Comparative Study on Electron Beam Characteristics of a Thermionic Electron Gun for Different Shapes of Wehnelt Cup - T. Abdulla, Roaa (Al-Nahrain Journal of Science, 2026)
This research paper presents a comparative study on the effect of the geometric design of a thermionic electron gun on the quality of the electron beam. Although several studies have been conducted on the thermionic electron gun design. However, the effect of the geometry of the Wehnelt electrode on the performance of the electron gun needs to be investigated through accurate and comparative analysis. Simulations were performed to test three different shapes of Wehnelt electrodes and their effect on electron gun performance behavior of the electron gun in which the characteristics of electron beams for different designs were analyzed with the aid of computer aided simulations. The results showed that the conical shape is the most efficient, producing low emittance (ԑ) and a small crossover diameter (R) of the electron beam. Based on these results, the performance of the electron gun can be improved by selecting an appropriate shape for the Wehnelt electrode, which produces high-quality electron beams.